الشراكة الاجنبية وأثرها على قطاع الصيدلة في الجزائر-دراسة حالة مجمع صيدال - عبد النور, سويد; صهيب, سلاطنة; عمارة, شلبي (University of eloued جامعة الوادي, 2022)
هدفت هذه الدراسة إلى إبراز اثر الشراكة الأجنبية على القطاع الصيدلاني في الجزائر، وأثرها على الاقتصاد الوطني وفقا للسياسة الوطنية للصحة التي تبنتها الحكومة الجزائرية قصد تخفيض فاتورة استيراد الأدوية، حيث كان للاتفاقيات الدولية والتحالفات الإستراتيجية دورا أساسيا في الشراكة التي اتبعتها الجزائر كإستراتيجية هامة لتطوير الصناعة الصيدلانية المحلية باكتساب المستثمر المحلي تكنولوجيا جديدة رغم وجود منافسة قوية في هذا السوق، حاولنا أيضا توضيح أهمية مناخ الاستثمار و مجمع صيدال في استمرار المشاريع الاستثمارية في القطاع الصيدلاني الذي كان النشاط فيه حكرا على الدولة الجزائرية باعتباره قطاعا حساسا يمس الأمن القومي"This study aimed to highlight the impact of foreign partnership on the pharmaceutical sector in Algeria and its impact onOn the national economy in accordance with the national health policy adopted by the Algerian government in order to reduce the import billMedicines, as international agreements and strategic alliances played a key role in the partnership that Algeria followed as a strategyImportant for the development of the local pharmaceutical industry by acquiring new technology by the local investor, despite the presence of strong competition in thisThe market, we also tried to clarify the importance of the investment climate and the legislative framework for business in the continuation of investment projects in the pharmaceutical sector, in which activity was the preserve of the Algerian state as a sensitive sector affecting national security. "
ماستر تجارة دولية
Keywords: الشراكة الأجنبية، قطاع الصيدلة، مجمع صيدال; foreign partnership, pharmacy sector, Saidal complex